2023
DOI: 10.59805/ebm.v1i1.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Shopping Lifestyle And Product Quality On Impulse Buying Fashion Hijab Squad Voal Paris Premium At Shopee

Abstract: The phenomenon of internet users is rapidly growing rapidly so that many changes are happening throughout the world among Indonesian people. The impact is enormous, so that fulfilling people's needs is easier and faster so that it becomes a potential market for e-commerce. Consumer behavior in Indonesia wants to shop with practical and easy transactions. Shopee is an E-Commerce Site that consumers can use as an option for shopping online. Monthly visitors to the E-Commerce Site in the third (third) quarter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…A person's lifestyle is influenced by impulsive purchases. This is consistent with the research conducted by Liantifa & Siswadhi, (2019); Maulana et al, (2019), Fardila et al (2023); Pratiwy & Siregar, (2022) which states that lifestyle shopping has a positive and significant influence on impulsive purchases. Supporting the role of shopping lifestyle, Lumintang (2012) stated that the higher a consumer's shopping style is hedonistic, the higher the rate of impulsive purchase of the person.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…A person's lifestyle is influenced by impulsive purchases. This is consistent with the research conducted by Liantifa & Siswadhi, (2019); Maulana et al, (2019), Fardila et al (2023); Pratiwy & Siregar, (2022) which states that lifestyle shopping has a positive and significant influence on impulsive purchases. Supporting the role of shopping lifestyle, Lumintang (2012) stated that the higher a consumer's shopping style is hedonistic, the higher the rate of impulsive purchase of the person.…”
Section: Introductionsupporting
confidence: 92%
“…(2023. Liantifa & Siswadhi, (2019), Maulana et al, (2019); Fardila et al (2023); Pratiwy & Siregar, (2022); who found that lifestyle shopping had a positive and significant influence on impulsive purchases. The study also supports the opinion of Assael (2001) The lifestyle is a world lifestyle expressed by one's activity, interests, and opinions.…”
Section: Shopping Life Style Has a Positive And Significant Effect On...mentioning
confidence: 99%